2019
DOI: 10.1002/ece3.5862
|View full text |Cite
|
Sign up to set email alerts
|

Opposite latitudinal patterns for bird and arthropod predation revealed in experiments with differently colored artificial prey

Abstract: The strength of biotic interactions is generally thought to increase toward the equator, but support for this hypothesis is contradictory. We explored whether predator attacks on artificial prey of eight different colors vary among climates and whether this variation affects the detection of latitudinal patterns in predation. Bird attack rates negatively correlated with model luminance in cold and temperate environments, but not in tropical environments. Bird predation on black and on white (extremes in lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 59 publications
4
70
3
1
Order By: Relevance
“…We found no evidence that latitude or climate influenced leaf-chewing herbivores, but we found that climatic factors rather than latitude per se were the best predictors of the large-scale variation in the incidence of leaf-miner and gall-inducer herbivores as well as in variation in leaf nutritional quality. In sharp contrast, we found no evidence that plant chemical defences and bird attack rates were influenced by latitude or climatic factors, which conflicts with the dominant view in ecology (Moles & Ollerton, 2016;Roslin et al, 2017;Zvereva et al, 2019). Because unravelling causes of latitudinal variation in the strength of biological interactions is one of the common approaches for the prediction of biotic interactions under global warming (Verheyen et al, 2019), it is crucial that future studies simultaneously test for effects of latitude per se and climate on insect herbivory by different feeding guilds (Kozlov et al, 2017), as well as investigate the mechanisms underlying such effects.…”
Section: Mechanisms Underlying Latitudinal and Climatic Variation In contrasting
confidence: 93%
See 3 more Smart Citations
“…We found no evidence that latitude or climate influenced leaf-chewing herbivores, but we found that climatic factors rather than latitude per se were the best predictors of the large-scale variation in the incidence of leaf-miner and gall-inducer herbivores as well as in variation in leaf nutritional quality. In sharp contrast, we found no evidence that plant chemical defences and bird attack rates were influenced by latitude or climatic factors, which conflicts with the dominant view in ecology (Moles & Ollerton, 2016;Roslin et al, 2017;Zvereva et al, 2019). Because unravelling causes of latitudinal variation in the strength of biological interactions is one of the common approaches for the prediction of biotic interactions under global warming (Verheyen et al, 2019), it is crucial that future studies simultaneously test for effects of latitude per se and climate on insect herbivory by different feeding guilds (Kozlov et al, 2017), as well as investigate the mechanisms underlying such effects.…”
Section: Mechanisms Underlying Latitudinal and Climatic Variation In contrasting
confidence: 93%
“…Third, we cannot exclude that the lack of latitudinal trend in bird attack rates resulted from methodological limitations due to the fact we only exposed green dummy caterpillars, in low hanging branches. Birds depend more on food accessibility than abundance per se, so that the exact location of dummy caterpillars regarding factors such as edge, light contrast and shrubby understory may have modified the perception and the accessibility to the prey (Zvereva et al, 2019). Thus, the absence of a latitudinal trend in bird predation cannot be inferred only from geographical location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (ca 85%) of all insects are tropical or from the southern hemisphere (Stork ), and the majority (ca 90%) of Lepidoptera are dietary specialists (Forister et al ). Recent evidence suggests that latitudinal patterns of bird and arthropod predation on Lepidopteran larvae are opposites, and that selection for prey colouration may vary geographically and according to predator identity (Zvereva et al ). To our knowledge, however, it has not yet been systematically investigated whether tropical species of moths have less variable colour patterns.…”
Section: Discussionmentioning
confidence: 99%